Usefulness of the Continuous Wavelet Transform for Evaluating Muscle Fatigue during Dynamic Contractions - NOGUCHI, Yoshio; TSURUSAKI, Toshiya; TOKUSHIMA, Hisao; HIGASHI, Toshio (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
Surface electromyography (SEMG) during an arm curl task was analyzed using the time-frequency technique of continuous wavelet transform (CWT) in order to evaluate muscle fatigue. Eleven healthy male volunteers performed arm curls with a 5kg dumbbell until exhaustion. SEMG was recorded from the biceps brachii muscle. Instantaneous mean frequency (IMF), median frequency (IMDF), and proportion of high-frequency components were calculated from coefficients of CWT, which was applied to six SEMG recordings of 1-s duration acquired at 5, 10, 15, 20, 25 and 30 trials of the task. The results showed that IMF and IMDF significantly shifted towards the lower frequency, and that the proportion of high-frequency components was significantly decreased. We were thus able to demonstrate a fluctuation in SEMG as a sign of muscle fatigue during dynamic contraction such as arm curls. The time-frequency analysis of SEMG using CWT is a useful method for evaluating muscle fatigue during dynamic contractions.